Lightweight concrete member
A lightweight concrete member using blast furnace cement B and specified aggregates with steel reinforcement addresses cracking resistance and CO2 emissions, ensuring flexibility and cost-effectiveness in concrete production.
Patent Information
- Application Number
- JP2023111414
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-06
- Publication Date
- 2025-01-20
AI Technical Summary
Existing concrete technologies using blast furnace cement B for reducing CO2 emissions face challenges in cracking resistance, especially in above-ground structures, and require separate equipment for different binders, limiting production flexibility and increasing costs.
A lightweight concrete member composed of blast furnace cement B, lightweight coarse aggregate, normal fine aggregate, water, and chemical admixtures, with a specified restraining material ratio of steel, reducing Portland cement use and optimizing cracking resistance without additional equipment needs.
The solution effectively reduces CO2 emissions, enhances cracking resistance, and maintains production flexibility while avoiding increased costs, making it suitable for above-ground structures.
Smart Images

Figure 2025008850000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a lightweight concrete member comprising lightweight concrete and a steel material. [Background technology]
[0002] In the field of concrete materials, technological development is underway to reduce the environmental impact. Specifically, by using blast-furnace slag cement type B as a concrete material, the amount of Portland cement used can be reduced, and CO2 emissions during cement production can be reduced. Examples of technologies that use Type B blast-furnace cement as a concrete material include the following:
[0003] Non-patent document 1 explains that for ordinary concrete using blast-furnace cement type B (specified in JIS A 5308:2019), shrinkage strain increases as the temperature rises, and crack resistance (especially at high temperatures of 30°C) decreases. In addition, Non-Patent Document 2 indicates that the crack resistance (especially at a high temperature of 30°C) of ordinary concrete using blast-furnace slag cement type B is improved by replacing part of the coarse aggregate of the ordinary aggregate with lightweight aggregate. The concrete after wet curing in which the coarse aggregate has been replaced with lightweight aggregate has a crack resistance of 0.2 to 0.3 N / mm 2 It is explained that this is effective in reducing shrinkage restraint stress because it introduces a compressive stress of about 100%, but that compressive stress does not change significantly when the replacement rate of lightweight aggregate is 25% or more by volume. In addition, it is explained that a replacement rate of lightweight aggregate of 25% by volume or less is desirable, even when taking into consideration the decrease in compressive strength due to an increase in the replacement rate, the stagnation of shrinkage restraint stress, and the decrease in the critical stress strength ratio. Furthermore, Non-Patent Document 3 indicates that, for ordinary concrete using blast-furnace slag cement type B, replacing some or all of the fine aggregate with lightweight aggregate, or replacing some of the fine and coarse aggregate with lightweight aggregate, improves crack resistance, as does Non-Patent Document 2, and introduces compressive stress after moist curing. Furthermore, Patent Document 1 proposes a technique for replacing part of the Portland cement in an ordinary concrete composition with blast-furnace cement type B, and replacing part or all of the coarse aggregate with lightweight aggregate. [Prior art documents] [Non-patent literature]
[0004] [Non-Patent Document 1] Japan Concrete Institute, "Report of the Research Committee on Shrinkage Cracking Reduction and Durability Improvement from the Viewpoint of Admixtures," pp.273-276, September 2010. [Non-Patent Document 2] Momose, Kanta, Yoda, Kasai, "Experimental Study on the Effect of Lightweight Aggregate on the Improvement of Shrinkage Cracking Resistance of Blast-furnace Slag Cement Concrete", Proceedings of the Japan Concrete Institute, Vol. 35, No. 1, pp. 589-594, 2013 [Non-Patent Document 3] Kiyohara, Imamoto, Arai, Ishikawa, "Experimental Study on Shrinkage Cracking Properties of Blast-furnace Cement Concrete Using Artificial Lightweight Aggregate," Proceedings of the Japan Concrete Institute, Vol. 37, No. 1, pp. 457-462, 2015 [Patent documents]
[0005] [Patent Document 1] JP 2011-116612 A Summary of the Invention [Problem to be solved by the invention]
[0006] When materials are measured at ready-mix concrete plants or precast concrete plants, cement and admixtures must be measured using separate measuring instruments for each material. Therefore, if two types of binders, Portland cement and blast-furnace cement type B, are to be used as in Patent Document 1, measuring instruments for each material must be secured. However, since the combination of each measuring instrument and the storage equipment such as material silos and storage bins connected to it is fixed, applying the technology of Patent Document 1 would require the exclusive use of these facilities, which would make it impossible to produce other types of concrete or limit the number of factories that can handle it.
[0007] The technologies disclosed in Non-Patent Documents 1 to 3 and Patent Document 1 are technologies related to normal concrete, and therefore normal aggregate is replaced with lightweight aggregate. In this case, as the replacement rate of lightweight aggregate, which has low rigidity and strength, increases, the elastic modulus and initial strength development decrease significantly. Therefore, in order to secure the same level of performance as that of general normal concrete, it is necessary to conduct a prior experiment to determine the optimal replacement rate that achieves both the required strength properties and the effect of improving crack resistance, as described in Non-Patent Document 2.
[0008] Concrete materials using blast-furnace cement type B described in Non-Patent Documents 1 to 3 and Patent Document 1 are more effective in terms of reducing CO2 emissions when applied to above-ground structures, which use a larger amount of concrete, than when applied to underground structures of buildings. However, above-ground structures have small cross-sections and dry easily, and concrete made with blast-furnace slag cement type B has a large shrinkage restraint force when drying, making it prone to cracking. For these reasons, concrete made with blast-furnace slag cement type B has rarely been used for above-ground structures.
[0009] Taking these circumstances into consideration, the inventors of the present invention wanted to create a lightweight concrete member that not only reduces CO2 emissions but also has excellent crack resistance so that it can be used for above-ground structures.
[0010] Therefore, an object of the present invention is to provide a lightweight concrete member that can reduce CO2 emissions and has excellent crack resistance. [Means for solving the problem]
[0011] The above problems can be solved by the following measures. The lightweight concrete member according to the present invention is a lightweight concrete member comprising lightweight concrete and a steel material, the lightweight concrete containing only blast furnace cement type B as cement and having a flow rate of 300 to 400 L / m 3 Lightweight coarse aggregate, normal fine aggregate, and 150-185kg / m 3 and a chemical admixture for concrete whose weight ratio relative to the B-type blast-furnace cement is 0.2 to 2.0%, and the restraining material ratio, which is the area ratio of the cross-sectional area of the steel material to the cross-sectional area of the lightweight concrete, is 0.2 to 8.0%. According to the present invention, only blast-furnace cement type B is used as cement, so the amount of Portland cement used can be reduced, and the amount of CO2 emissions during cement production can be reduced. In addition, according to the present invention, the content of lightweight coarse aggregate and the restraining material ratio are specified, so that excellent crack resistance can be achieved. According to the present invention, since the use of lightweight concrete is assumed and lightweight coarse aggregate is used as the coarse aggregate, there is no need for extra consideration such as optimization of the replacement rate as in Non-Patent Document 2. Furthermore, according to the present invention, since the equipment used for manufacturing normal lightweight concrete can be used, the above-mentioned equipment problems expected in the technology according to Patent Document 1 do not occur. In addition, in Non-Patent Documents 2-3 and Patent Document 1, the ordinary aggregate of normal concrete is replaced with an expensive lightweight aggregate, so the unit price of concrete increases significantly from the original unit price, but in the present invention, there is no need to change the aggregate of lightweight concrete (it remains lightweight coarse aggregate), and there is no problem of the unit price of concrete changing significantly. Based on these points, it can be said that the present invention is a technology with higher feasibility and practicality than the technologies according to Non-Patent Documents 1-3 and Patent Document 1.
[0012] The lightweight concrete member according to the present invention has a compressive stress of 0.01 to 0.33 N / mm during the wet curing period of 3 to 22 days. 2 It is preferable that: According to the present invention, since the compressive stress generated during the moist curing period is specified, excellent crack resistance can be exhibited more reliably.
[0013] The lightweight concrete member according to the present invention is preferably used for floor slabs, beams, columns, walls, and curtain walls. According to the present invention, excellent crack resistance can be exhibited, and therefore the material can be suitably applied as a predetermined member (predetermined application). Effect of the Invention
[0014] The lightweight concrete member according to the present invention can reduce CO2 emissions and has excellent crack resistance. [Brief description of the drawings]
[0015] [Figure 1] FIG. 2 is a schematic diagram of a test specimen used for calculating compressive stress. [Diagram 2] 1 is a graph showing the measurement results of the restraint stress of each test specimen. [Diagram 3] 13 is a graph showing the measured and calculated values of the work load per unit lightweight coarse aggregate of a test specimen having a restraining material ratio of 4.0%. [Figure 4A] This is a graph plotting the measured values of the restraint ratio and restraint stress for each specimen, as well as the calculated values when the reduction factor in Equation 1 is invalid. [Figure 4B] This is a graph plotting the measured values of the restraint ratio and restraint stress for each specimen, as well as showing the calculated values when the reduction coefficient in Equation 1 is enabled. [Figure 5A] This is a graph showing the results of the restraint stress for specimen A4 and specimen A in the crack resistance test. [Figure 5B]This is a graph showing the results of the restraint stress for specimens b4 and b in the crack resistance test. [Figure 6] This is a graph in which the results of the restraining stress when the restraining material ratio is 8.0% are added to the graph of FIG. 4B. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] Hereinafter, an embodiment (the present embodiment) for carrying out a lightweight concrete member according to the present invention will be described. [Lightweight concrete members] The lightweight concrete member in this embodiment is a lightweight concrete member comprising lightweight concrete and steel, and the lightweight concrete contains only type B blast-furnace slag cement as cement, as well as lightweight coarse aggregate, ordinary fine aggregate, water, and a chemical admixture for concrete, and has a restraining material ratio within a specified range. Below, each element constituting the lightweight concrete member according to this embodiment will be described.
[0017] [Lightweight concrete] The lightweight concrete member according to this embodiment includes "lightweight concrete" and "steel". The lightweight concrete is concrete that uses lightweight aggregate as the aggregate, and more specifically, satisfies the requirements stipulated in JIS A 5308:2019. The lightweight concrete is preferably lightweight concrete type 1 (so-called lightweight type 1) that uses lightweight coarse aggregate as the coarse aggregate and ordinary fine aggregate as the fine aggregate. (Blast-furnace cement type B) Lightweight concrete contains only blast-furnace slag cement type B. Because lightweight concrete contains blast-furnace slag cement type B, it is possible to reduce the amount of Portland cement used, and therefore the amount of CO2 emissions during cement production. Here, type B blast furnace cement is cement mixed with a specified amount of blast furnace slag and meets the requirements specified in JIS R 5211:2019. And, "containing only blast furnace cement type B as cement" means that no cement such as Portland cement (JIS R 5210:2019) is used other than blast furnace cement type B. In other words, the lightweight concrete according to this embodiment is different from general lightweight concrete in that all cement is replaced with blast furnace cement type B. The content (unit amount) of blast furnace cement type B in lightweight concrete is, for example, 280 kg / m 3 More than 300kg / m 3 More than 330kg / m 3 More than 400kg / m 3 Below 380kg / m 3 Below 360kg / m 3 The following is the result.
[0018] (Lightweight coarse aggregate) Lightweight coarse aggregate is a coarse aggregate that is lighter than ordinary coarse aggregate and meets the requirements set forth in JIS A 5002:2003. The content (unit amount) of lightweight coarse aggregate in lightweight concrete is, for example, 300 L / m 3 Above, 305L / m 3 Above, 309L / m 3 More than 400L / m 3 Below, 380L / m 3 Below, 350L / m 3 The following is the result. (Normal fine aggregate) Ordinary fine aggregates include mountain sand, crushed lime sand, river sand, sea sand, crushed sand, silica sand, and lime sand, and comply with JIS A5308:2019 Appendix A. The content (unit amount) of ordinary fine aggregate in lightweight concrete is, for example, 300 L / m 3 Above, 320L / m 3 Above, 330L / m 3 More than 450L / m 3 Below, 400L / m 3 Below, 360L / m 3 The following is the result.
[0019] (water) The water content (unit amount) of lightweight concrete is, for example, 150 kg / m 3 More than 170kg / m 3 More than 180kg / m 3 Above 185kg / m 3 The following is the result. The water is not particularly limited, and tap water, groundwater, industrial water, etc. can be used. (Chemical admixture for concrete) Chemical admixtures for concrete are defined in JIS A 6204:2011 as air-entraining agents, air-entraining water-reducing agents, and high-performance air-entraining water-reducing agents. The weight ratio of the chemical admixture for concrete (at least one of AE water reducing agent and high performance AE water reducing agent) to blast-furnace cement Type B (= weight of admixture / weight of blast-furnace cement Type B × 100) in lightweight concrete is, for example, 0.2% or more and 2.0% or less, 1.5% or less, or 1.0% or less. (others) The lightweight concrete according to this embodiment may contain, as appropriate, conventionally known materials used in general lightweight concrete, as long as the desired effects of the present invention are not impaired.
[0020] [Steel] Steel materials are reinforcing materials such as steel frames (shaped steel) and reinforcing bars (steel bars) that mainly bear tensile stress, and act as restraining materials to restrain the expansion of lightweight concrete that occurs during the moist curing period. By restraining the expansion of the lightweight concrete with the steel materials, compressive stress (prestress) is applied to the lightweight concrete members. The type of steel material is not particularly limited as long as it is a general steel material used for the applications described below. The location of the steel material in the lightweight concrete member is also not particularly limited, and the steel material may be placed inside the lightweight concrete, around the lightweight concrete, or both. When the steel material is placed inside the lightweight concrete, internal restraint is applied, and when the steel material is placed around the lightweight concrete, external restraint is applied. (Restraint material ratio) The restraining ratio, which is the ratio of the cross-sectional area of the steel to the cross-sectional area of the lightweight concrete, is preferably 0.2% or more. The restraining ratio is preferably 8.0% or less, more preferably 5.0% or less, and more preferably 4.0% or less. By keeping the restraining ratio within the specified range, appropriate compressive stress is generated (the compressive stress described below is within the specified range), and excellent crack resistance can be exhibited. The restraint ratio is, in detail, the ratio of the cross-sectional areas in the principal stress direction (= cross-sectional area of steel material / cross-sectional area of lightweight concrete x 100). For example, if the cross section of the steel material in the principal stress direction is 200 mm 2 The cross section of the lightweight concrete member (lightweight concrete + steel) is 8200 mm 2 In this case, the restraint ratio is 2.5% (=200 / (8200-200)×100). In addition, when calculating the restraint ratio, the term "steel material" refers to a concept that includes all steel materials, and naturally includes main reinforcing bars.
[0021] Compressive Stress The compressive stress generated during the wet curing period of 3 to 22 days is 0.01 N / mm 2 By having a compressive stress of a predetermined value or more, it is possible to more reliably obtain excellent crack resistance. In addition, the compressive stress is preferably 0.33 N / mm 2 The following is preferable. By having the compressive stress be equal to or less than a predetermined value, it is possible to avoid occurrence of a situation in which the compressive strength is reduced. Here, the effective age is the age of the material calculated so that the effect of the curing temperature on the hydration reaction is equivalent to the degree of hydration when the curing temperature is 20°C, as specified on page 68 of the Architectural Institute of Japan's "Guidelines and Commentary on Thermal Crack Control Design and Construction of Mass Concrete, Second Edition."
[0022] Specifically, the compressive stress can be calculated based on the following Equations 1 and 2. The following formulas 1 and 2 were derived by the inventors based on the results of experiments, with reference to the formulas described in "Fundamental Study on the Use of Chemical Prestress in Concrete" by Yukikazu Tsuji (Proceedings of the Japan Society of Civil Engineers, No. 235, March 1975). ≪Formula 1≫ σex=-α[{2×Er×(pr / 100)} 0.5 ]×[(Ug×Vg) 0.5 ]+β (Explanation of symbols in formula 1) σex: Compressive stress (N / mm2) caused by expansion of lightweight concrete restrained by steel during wet curing 2 ) [Negative restraint stress is considered to be compressive stress] Er: Young's modulus of the restraining material (steel) (N / mm 2 ) pr: restraining material ratio (%) [=Ar / Ac×100] Ar: Cross-sectional area of the restraining material (steel) in the principal stress direction (mm 2 ) Ac: Cross-sectional area of lightweight concrete in the direction of principal stress (mm 2 ) Ug: Work load per unit lightweight coarse aggregate during moist curing period te (days) ([N / mm 2 ]·[L / m 3 ] -1 ), (Here, the "work load per unit of lightweight coarse aggregate" refers specifically to the "work load per unit volume of lightweight coarse aggregate on the restraining material.") Vg: Lightweight concrete 1m 3 Lightweight aggregate volume per unit (L / m 3 ) α, β: Reduction coefficient when considering compressive stress safety When the reduction coefficients are to be invalidated, α=1.0 and β=0.0 may be used, and when the reduction coefficients are to be valid, for example, α=0.9 and β=−0.03 may be used. The work load Ug per unit lightweight coarse aggregate during the moist curing period te in the above formula 1 can be calculated based on the following formula 2.
[0023] ≪Formula 2≫ Ug = Uref × exp[1.15 × {1-(7 / te) 0.65}] (Explanation of symbols in formula 2) Uref: Reference work load (N / mm 2 )·(L / m 3 ) -1 te: Period of moist curing converted into effective age (days) The reference work load Uref represents the value for a moist curing period (effective age) of 7 days when the restraining material ratio is 4.0%, and is 9.27 × 10 -9 (N / mm 2 )·(L / m 3 ) -1 Let us assume that. The value of Uref and the constants (1.15, 0.65) in formula 2 were determined by the least squares method so that the solid line in FIG. 3 (calculated values of Ug) approached the plot in FIG. 3 (measured values of Ug).
[0024] [Application] The lightweight concrete member according to the present embodiment has excellent crack resistance and can be suitably applied to above-ground structures such as "floor slabs," "beams," "columns," and "walls." Among above-ground structures, it can also be applied to precast concrete (precast concrete curtain walls, etc.) that is manufactured in advance in a factory or the like. For example, when manufacturing a curtain wall, it may be manufactured using a general manufacturing method, but in order to prevent the surface of the component from drying out, a low-permeability sheathing will be left in place or the component will be covered with a watertight sheet and then subjected to moist curing for a specified period of time. EXAMPLES
[0025] [Example 1: Test to confirm the validity of the calculation method for compressive stress] (Preparation of specimen) FIG. 1 is a schematic diagram of the test specimen used to calculate the compressive stress. The shape of the test specimen was based on Method B of Appendix B of JIS A 6202:2017, "Test method for restrained expansion and shrinkage of expansive concrete," as shown in Figure 1. In detail, the lightweight concrete 1 was 100mm high x 100mm wide x 385mm long, and a restraining material 2 (SS400) was embedded inside the lightweight concrete 1, and both left and right ends of the lightweight concrete 1 were restrained with nuts 3 (NACH10T) and end plates 4 (SS400, length 19mm). A strain gauge 5 was placed near the center of the restraining material 2. The restraining material ratio was changed by using restraining materials 2 with different diameters (nominal diameters: M6, M12, M24). The materials of the lightweight concrete used in the test specimens are as shown in Table 1, and the composition is as shown in Table 2. As shown in Table 2, the temperature during the moist curing period from the time the concrete was mixed (simply referred to as temperature in the table) was set to two levels, 20°C and 30°C, and the restraint material ratio was set to three levels, 0.2%, 0.9%, and 4%, and two specimens were prepared for each of the six types of test specimens (a1 to a3, b1 to b3). After casting, the specimens were covered to prevent the surfaces from drying out.
[0026] [Table 1]
[0027] [Table 2]
[0028] (Test contents: Regarding Figure 2) FIG. 2 is a graph showing the measurement results of the restraint stress of each test specimen. The "restraint stress" of each specimen during the wet curing period was calculated by multiplying the Young's modulus of the restraint material (20.5 kN / mm 2 ) and the ratio of the cross-sectional area of the steel and lightweight concrete (= cross-sectional area of steel / cross-sectional area of lightweight concrete), and then the obtained values for the two specimens were averaged to calculate the strain. The strain of the restraining material was measured up to an age of 14 days. In order to evaluate the effect of different moist curing temperatures on this "restraint stress" at equivalent material ages, the material ages were converted to effective material ages. If the measurement period up to 14 days is converted to effective material ages, it is 14 days at 20°C and 22 days at 30°C. The "restraint stress" and "effective material age" of each specimen calculated in this manner are plotted and shown in Figure 2. In addition, the compressive stress in FIG. 2 is shown as a negative restraint stress.
[0029] (Test contents: Regarding Figure 3) FIG. 3 is a graph showing the measured and calculated values of the work load per unit lightweight coarse aggregate of a test specimen with a restraining material ratio of 4.0%. For specimens a3 and b3 with a restraint ratio of 4.0%, data was extracted for the specified moist curing periods (effective ages of 3, 5, 7, 11, and 22 days) from the time-dependent data on the restraint stress (values shown in Figure 2) obtained using the method described above, and the average value of the restraint stress for specimens a3 and b3 was calculated. Then, the extracted data was substituted for the compressive stress σex in the above formula 1 (α=1.0, β=0.0) to calculate the workload Ug per unit lightweight coarse aggregate. The values of Ug calculated in this manner were plotted as measured values in Figure 3. The calculated values of the amount of work Ug per unit of lightweight coarse aggregate obtained based on the above-mentioned formula 2 are also shown by a line in Figure 3.
[0030] (Test contents: Regarding Figure 4) FIG. 4 is a graph plotting the measured values of the restraint ratio and the restraint stress of each specimen. FIG. 4A is a graph also showing the calculated values when the reduction coefficient of Equation 1 is disabled, and FIG. 4B is a graph also showing the calculated values when the reduction coefficient of Equation 1 is enabled. For each specimen, data for the specified moist curing period (effective age of 3, 5, 7, 11, and 22 days) was extracted from the time-dependent data of the restraint stress (values shown in Figure 2) obtained by the above method. Then, the average value of the restraint stress of specimens with the same restraint ratio was calculated for each specified moist curing period (i.e., the average value of the restraint stresses of a1 and b1, a2 and b2, and a3 and b3). The restraint ratio and restraint stress of each specimen calculated in this manner are plotted in Figures 4A and 4B. Also, Fig. 4A shows a curve of the restraint ratio and the restraint stress obtained based on the above formula 1 with the reduction coefficients disabled (α = 1, β = 0), while Fig. 4B shows a curve of the restraint ratio and the restraint stress obtained based on the above formula 1 with the reduction coefficients enabled (α = 0.9, β = -0.03).
[0031] (Discussion of the results shown in FIG. 2 of Example 1) The results in Figure 2 confirm that the compressive stress increases as the restraint ratio increases, and that the compressive stress increases as the effective material age increases. Furthermore, according to the results shown in Figure 2, it was confirmed that the compressive stress values were almost the same between specimens a1 and b1, a2 and b2, and a3 and b3, which had different temperatures during the moist curing period. Therefore, it was confirmed that compressive stress can be expressed by the "restraint ratio" and "effective age" by using the effective age and taking into account the effect of temperature during the moist curing period. (Discussion of the results shown in FIG. 3 of Example 1) According to the results in Figure 3, the measured and calculated values of the work load Ug per unit lightweight coarse aggregate were consistent, confirming that Ug can be appropriately calculated based on Equation 2. (Discussion of the results shown in FIG. 4 of Example 1) According to the results in Figure 4A, the measured compressive stress values and the calculated values (when the reduction factor in Equation 1 was disabled) were almost identical, but it was confirmed that the calculated values were sometimes higher when the restraint ratio was less than 1%. On the other hand, the results in Figure 4B confirm that, regardless of the restraint ratio, the calculated compressive stress (when the reduction factor in Equation 1 is enabled) is consistently lower than the measured value. In other words, from the results in Figures 4A and 4B, it was found that the compressive stress can be appropriately calculated based on Equation 1 when the reduction coefficient is disabled, but if it is desired to calculate the compressive stress on the safer side (if it is desired to make the actual compressive stress larger than the calculated compressive stress), it is preferable to enable the reduction coefficient in Equation 1. From the above, based on all the results of Example 1 shown in FIGS. 2 to 4, it was confirmed that the compressive stress can be calculated very simply and easily based on Equations 1 and 2.
[0032] [Example 2: Test to confirm crack resistance, etc.] (Preparation of specimen) The materials used for the lightweight concrete of specimens a4 and b4 are shown in Table 1. On the other hand, the materials used for the lightweight concrete of specimens a and b are "ordinary Portland cement (density: 3.16 (g / cm 3 ), specific surface area 3250(cm 2 The materials used were those shown in Table 1, except for the material (N) used for the sintered body (100 g / g)) (represented by the symbol N in the table). The composition of each specimen was as shown in Table 3.
[0033] (Test content: Crack resistance test) The crack resistance test was carried out in accordance with the "Test method for evaluating shrinkage cracks in concrete" described in the above-mentioned Non-Patent Document 2, and the details are as follows. The specimen used in the crack resistance test was lightweight concrete with dimensions of 100mm height x 100mm width x 1,100mm length, and a threaded steel material with a nominal diameter equivalent to M33 (restraint material ratio 8.0%) was embedded as a restraint material in the center of the 100mm x 100mm cross section. A Teflon (registered trademark) sheet was used to remove adhesion to the lightweight concrete in the central 300mm section of the restraint material, and a strain gauge was placed in the center of the restraint material. The shape of the specimen was that of the lightweight concrete 1 in Figure 1 without nuts 3 or end plates 4 at both ends. The prepared specimens were demolded after 7 days of wet curing, and then covered with aluminum tape on all sides except for the two sides of the 100 mm high x 1,100 mm long specimen, and dried under the conditions shown in Table 3. The "restraint stress" of each specimen was calculated by multiplying the Young's modulus of the restraint material (20.5 kN / mm) by the strain of the restraint material measured with a strain gauge. 2 ) and the ratio of the cross-sectional areas of the steel and lightweight concrete (= cross-sectional area of steel / cross-sectional area of lightweight concrete). The crack resistance tests were carried out on two specimens for each test piece.
[0034] (Test content: Strength property test) For the lightweight concrete specimens at 28 days of age, compressive strength tests were conducted according to the method described in JIS A 1108:2018, static elastic modulus tests were conducted according to the method described in JIS A1149:2017, and splitting tensile strength tests were conducted according to the method described in JIS A 1113:2018. In addition, these tests were carried out on three specimens for each test piece, and the average value was calculated.
[0035] [Table 3]
[0036] [Table 4]
[0037] (Consideration of strength properties shown in Table 4 of Example 2) According to the test results on the strength properties in Table 4, for specimens a4 and b4 which satisfy the requirements of the present invention, the splitting tensile strength of specimen a4 was slightly lower, but the other values were equivalent to those of conventional lightweight concrete (specimens a and b).
[0038] (Discussion of the results of the crack resistance test shown in Table 4 and FIG. 5 of Example 2) FIG. 5 shows the results of the restraint stress in the crack resistance test, with FIG. 5A showing the results for specimen a4 and specimen a, and FIG. 5B showing the results for specimen b4 and specimen b. In addition, "x" in FIG. 5 indicates that a crack occurred. According to the results in Figures 5A and 5B, compressive stress during the moist curing period occurred in the conventional lightweight concrete (specimens a and b), but it was found that the compressive stress was slightly larger in specimens a4 and b4 that satisfied the requirements of the present invention. The tensile stress after drying started was 2 to 2.5 N / mm for conventional lightweight concrete (specimens a and b). 2 whereas specimens a4 and b4, which satisfy the requirements of the present invention, are 0.5 to 1.5 N / mm 2 and it was confirmed that it was significantly suppressed. Therefore, as shown in Table 4 and Figures 5A and 5B, the time until cracks occurred for specimen a4 (experimental condition temperature 20°C) satisfying the requirements of the present invention was significantly longer than that for the conventional lightweight concrete (specimen a). Even at the high experimental temperature of 30°C, the time until cracks occurred for specimen b4 satisfying the requirements of the present invention was equal to or longer than that for the conventional lightweight concrete (specimen b). In other words, it was confirmed that by satisfying the requirements of the present invention, the lightweight concrete member can exhibit excellent crack resistance.
[0039] (Discussion of the results shown in FIG. 6 of Example 2) FIG. 6 is a graph in which the results of the restraining stress when the restraining material ratio is 8.0% are added to the graph of FIG. 4B. The results added to Figure 6 are the average values of the restraint stress obtained in the test of Example 2 for specimens a4 and b4 used in the crack resistance test, calculated for each specified wet curing period (effective age of 3, 5, 7, 11, and 22 days). According to the results in Fig. 6, it was confirmed that the calculated compressive stress was lower than the measured value, even when the restraint ratio was 8.0%. Therefore, from the results in Fig. 6, it was found that even when the restraint ratio is 8.0%, the compressive stress can be calculated on the safer side based on Equation 1 when the reduction coefficient is enabled (α=0.9, β=-0.03). In other words, when the compressive stress calculated based on Equation 1 (when the reduction coefficient is enabled) is greater than the lower limit value specified in the present invention, the actual compressive stress will naturally be greater than the lower limit value, so that excellent crack resistance can be more reliably exhibited. [Explanation of symbols]
[0040] 1. Lightweight concrete 2 Restraint material (steel material) 3 Nut 4 End plate 5 Strain gauge
Claims
1. A lightweight concrete member comprising lightweight concrete and a steel material, The lightweight concrete contains only blast furnace cement type B as cement and has a viscosity of 300 to 400 L / m 3 Lightweight coarse aggregate, normal fine aggregate, and 150-185 kg / m 3 and a chemical admixture for concrete in a weight ratio of 0.2 to 2.0% relative to the blast-furnace cement type B, A lightweight concrete member characterized in that a restraining material ratio, which is the area ratio of the cross-sectional area of the steel material to the cross-sectional area of the lightweight concrete, is 0.2 to 8.0%.
2. The compressive stress generated during the wet curing period of 3 to 22 days of effective age is 0.01 to 0.33 N / mm 2 2. The lightweight concrete member according to claim 1,
3. 3. The lightweight concrete member according to claim 1 or 2, which is used for a floor slab, a beam, a column, a wall, or a curtain wall.
Citation Information
Patent Citations
Environmental load-reducing concrete composition
JP2011116612A